2022
DOI: 10.18632/aging.203826
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in patients with Alzheimer’s disease spectrum: a systematic review and meta-analysis

Abstract: Context: Gut dysbiosis has been proposed as one of pathologies in patients with Alzheimer’s disease (AD) spectrum. Despite such enthusiasm, the relevant results remain substantially controversial. Objective: A systematic review and meta-analysis were performed to investigate the differences of gut microbiota (GM) between patients with AD spectrum (including mild cognitive impairment [MCI] and AD) and healthy controls (HC). Data sources: PubMed, MEDLINE, Scopus, and Cochrane Library from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 72 publications
6
57
1
Order By: Relevance
“…Guo et al reported that patients with AD had increased Prevotella at the genus level compared with healthy controls [ 51 ]. Phascolarctobacterium can produce short-chain fatty acids, including acetate and propionate, and is more abundant in the AD spectrum [ 52 ]. Bifidobacterium is a dominant genus in the human gut, and both decrease and increase in abundance in AD patients have been reported [ 48, 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al reported that patients with AD had increased Prevotella at the genus level compared with healthy controls [ 51 ]. Phascolarctobacterium can produce short-chain fatty acids, including acetate and propionate, and is more abundant in the AD spectrum [ 52 ]. Bifidobacterium is a dominant genus in the human gut, and both decrease and increase in abundance in AD patients have been reported [ 48, 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported the abundances of Proteobacteria and Gammaproteobacteria were higher in participants with MCI when compared with those in healthy controls. A meta-analysis further showed that the abundance of the Proteobacteria phylum increased progressively from an NC group to a MCI and an AD group ( Hung et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies [ 23 , 24 , 25 , 26 ], we set the inclusion and exclusion criteria. Randomized controlled trials were included if they met the following inclusion criteria: (1) participants with clinical diagnosis of dementia or cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%